1991
DOI: 10.1152/jn.1991.65.1.76
|View full text |Cite
|
Sign up to set email alerts
|

Gustatory neural coding in the monkey cortex: stimulus intensity

Abstract: 1. We analyzed the activity of single neurons in gustatory cortex of alert cynomolgus monkeys in response to a range of stimulus intensities. Chemicals were deionized water, fruit juice, and several concentrations of the four prototypical taste stimuli: 10(-3)-1.0 M glucose, 10(-3)-1.0 M NaCl, 10(-4)-3 x 10(-2) M HCl, and 10(-5)-3 x 10(-3) M quinine HCl. 2. Taste-evoked responses could be recorded from a cortical gustatory area that measured 2.5 mm in its anteroposterior extent, 6.0 mm dorsoventrally, and 3.0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
55
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(63 citation statements)
references
References 0 publications
8
55
0
Order By: Relevance
“…Electrophysiological studies with rodents or nonhuman primates have shown that increasing the stimulus concentration would usually produce an increase in the firing rate. At the GC level, our results are consistent with the majority of both behavior and electrophysiological experiments (Yaxley et al, 1990;Scott et al, 1991) (but see Stapleton et al, 2006). In fact, we measured the responses to three increasing NaCl concentrations, and we found a monotonic increase in the maximum amplitude and in the size of the response (Fig.…”
Section: Spatial Coding Of Concentration Dependencesupporting
confidence: 90%
“…Electrophysiological studies with rodents or nonhuman primates have shown that increasing the stimulus concentration would usually produce an increase in the firing rate. At the GC level, our results are consistent with the majority of both behavior and electrophysiological experiments (Yaxley et al, 1990;Scott et al, 1991) (but see Stapleton et al, 2006). In fact, we measured the responses to three increasing NaCl concentrations, and we found a monotonic increase in the maximum amplitude and in the size of the response (Fig.…”
Section: Spatial Coding Of Concentration Dependencesupporting
confidence: 90%
“…These neurons were very broadly tuned, possessing an average entropy of H ϭ 0.971 Ϯ 0.007 (n ϭ 61). Previous single unit recordings from GC in awake or anesthetized rats have found average entropy values of 0.54 (Yamamoto et al, 1984(Yamamoto et al, , 1989, which approximately matches the 0.56 -0.75 found in awake, nonhuman primates (Yaxley et al, 1990;Scott et al, 1991;Smith-Swintosky et al, 1991). That our entropies were higher than those previously reported can be rationalized, in part, by noting that the gustatory responses often differ significantly from baseline for only a few milliseconds (Figs.…”
Section: Chemosensory Neuronssupporting
confidence: 85%
“…From the three examples given in Figures 7, 9, and 11, it is seen that the GC responses to increases in concentration were not simply a corresponding monotonic increase in firing rate as was found in some (Yaxley et al, 1990;Scott et al, 1991) but not all (Yamamoto et al, 1984) studies. Rather, neurons often exhibited complex responses to changes in concentration.…”
Section: Responsiveness Of Gc Neurons To Changes In Concentrationmentioning
confidence: 72%
“…Ito et al (2001) also noted that reaction time decreased with increases in tastant concentration in subhuman primates; however, the onset latencies of neuronal responses in the PGA (area 3, area G and other cortical areas) were not affected by changes in NaCl concentrations. Scott et al (1991) also noted that, in the macaque, the activity of single cortical neurons increased response magnitudes with increasing tastant concentration, whereas the onset latency for these neurons did not change significantly. The present findings detailing the relationship between NaCl concentrations and the response magnitudes and latencies of the neuronal activity in human area G are consistent with the results obtained from the PGA in monkeys.…”
Section: Temporal Aspects Of Cortical Activity and Stimulus Concentramentioning
confidence: 82%